How to train your dragon book 2 : how to be a pirate - Cowell, Cressida (New York : Little, Brown and Company, 2010)
Hiccup Horrendous Haddock III and his fellow Viking trainees set out to discover a treasure chest guarded by a dead man$1 (Bs ghost and learn important lessons about being a hero.s
Originally published in the U.K. by Hodder Children$1 (Bs Books, 2004.s
Keywords: Vikings -- Fiction; Dragons -- Fiction; Pirates -- Fiction; Treasure -- Fiction; Friendship -- Fiction; Humorous stories